2013
DOI: 10.1116/1.4807902
|View full text |Cite
|
Sign up to set email alerts
|

Advances in silicon carbide science and technology at the micro- and nanoscales

Abstract: Advances in siliconcarbide microfabrication and growth process optimization for siliconcarbide nanostructures are ushering in new opportunities for microdevices capable of operation in a variety of demanding applications, involving high temperature, radiation, or corrosive environment. This review focuses on the materials science and processing technologies for siliconcarbidethin films and low dimensional structures, and details recent progress in manufacturing technology, including deposition, metallization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
80
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(80 citation statements)
references
References 270 publications
0
80
0
Order By: Relevance
“…The NV − center in diamond is the most studied defect for quantum technologies, so that its properties, strengths and limitations are by now very well understood. Deep defect centers in silicon carbide (SiC) have emerged as strong contenders due to this material's significantly lower cost, availability of mature microfabrication technologies [6,7], and favorable optical emission wavelengths [8].…”
mentioning
confidence: 99%
“…The NV − center in diamond is the most studied defect for quantum technologies, so that its properties, strengths and limitations are by now very well understood. Deep defect centers in silicon carbide (SiC) have emerged as strong contenders due to this material's significantly lower cost, availability of mature microfabrication technologies [6,7], and favorable optical emission wavelengths [8].…”
mentioning
confidence: 99%
“…SiC has particularly attractive features, including significantly lower cost and mature microfabrication. [14][15][16][17][18][19] A number of defects in silicon carbide (SiC) have significant potential including the antisite-vacancy defect, 3,20 the Si vacancy, 10,12,13,[21][22][23][24][25][26][27][28][29][30][31][32][33] and the divacancy. 7,9,[34][35][36] Experiments have shown that some of these defects can have similar coherence and optical manipulation properties as NV centers.…”
mentioning
confidence: 99%
“…Silicon carbide (SiC) is widely used in high-temperature structural materials, protective coatings, and semiconductor devices [1]. SiC has more than 200 polytypes, including zinc blend-type cubic (3C) and many hexagonal structures such as 2H, 4H, 6H, and 15R because of a wide variety of stacking sequence of the Si-C bilayer.…”
Section: Introductionmentioning
confidence: 99%
“…Films of 3C-SiC are mostly obtained by CVD at a wide range of deposition temperatures (1373-2673 K), except for epitaxial growth of 4H-and 6H-SiC films on single-crystal substrates [1,10,11]. Although 2H-SiC may be stable at less than 1673 K [12], 2H-SiC films have never been synthesized by CVD.…”
Section: Introductionmentioning
confidence: 99%